John Taylor’s Philippine Insurrection against the United States: A preliminary digital interrogation of the archivist - Sy, Nicholas Michael C. (Philippine Social Sciences Review, 2021)
John Taylor’s five-volume documentary collection The Philippine Insurrection against the United States is an invaluable resource on the Philippine-American War. However, the criteria with which Taylor selected the documents for his collection have remained opaque. The present methodological paper explores the use of Topic Modeling, a tool from the Digital Humanities, to posthumously interrogate the archivist. By comparing the preliminary results of successive manual and automatic coding, its findings highlight the crucial role that materials external to a corpus play in helping the researcher to gauge whether or not particular strings of co-occurrent words are relevant to a research project.
Keywords: Philippine-American War, Digital Humanities, Topic Modeling, MALLET, History